Production of silica aerogel microparticles loaded with ammonia borane by batch and semicontinuous supercritical drying techniques - Rueda, Miriam (2014)
Silica aerogel microparticles were prepared by supercritical drying and used as support for hydrogen-storing ammonia borane (AB). The formation of aerogel microparticles was done using two different processes: batch supercritical fluid extraction and a semicontinuous drying process. Silica aerogel microparticles with a surface area ranging from 400 to 800 m2/g, a volume of pores of 1 cm3/g, and a mean particle diameter ranging from 12 to 27 μm were produced using the two drying techniques. The particle size distribution (PSD) of the microparticles was influenced by shear rate, amount of catalyst, hydrophilic–hydrophobic solvent ratio and hydrophobic surface modification. In particular, irregular aerogel particles were obtained from hydrophilic gels, while regular, spherical particles with smooth surfaces were obtained from hydrophobic gels. AB was loaded into silica aerogel microparticles in concentrations ranging from 1% till 5% wt. Hydrogen release kinetics from the hydride-loaded aerogel was analyzed with a volumetric cell at 80 °C. By stabilization of AB into the silica aerogel microparticles, an improvement of the release rate of hydrogen from AB was observed.